Orthogonal Transforms for Digital Signal and Image Processing - Sarukhanyan, Hakob (Mathematical Problems of Computer Science, 2021)
In this report there are presented some primary results obtained in Digital Signal and Image Processing laboratory of the Institute for Informatics and Automation Problems of NAS RA.